Student anti-war protest - Spartan Daily, Kioski:::Creator::::::::::::
Student anti-war protest at San Jose State College. One student holds a sign that reads: If we would keep our dirty bloody dollar crooked fingers out of the business of these nations so full of depressed exploited people they will arrive at a solution of their own. General David M. Shoop, former commandant U.S. Marines and Medal of Honor winner (from a speech to the U.S. Congress, Feb. 21, 1967[?])